Efek Pemberian Ekstrak Etanol Daun Sembukan (Paederia foetida L.) Terhadap Penurunan Kadar Asam Urat Tikus Putih (Rattus norvegicus) Jantan - Suwahyuni Mus; Maulita Indrisari; Fadhillah Maryam; Surida Surida (Jurnal Fitofarmaka Indonesia, 2022)
Sembukan leaf is a medicinal plant that is widely used by the community, one of which is as an anti-inflammatory. This study aims to determine the effect of giving sembukan leaves (Paederia foetida L.) to decrease uric acid levels in male white rats (Rattus norvegicus). The study was carried out by testing 5 groups of white rats, namely positive control (Allopurinol 100 mg), negative control (Na.CMC suspension 0.5%), the dose of ethanol extract of sembukan leaves 10 mg/KgBB, 20 mg/KgBB, and 40 mg/KgBB. Each treatment group measured initial uric acid levels (before induction), after induction of chicken liver juice and after giving treatment or test samples using test strips. The results showed that uric acid levels in all groups decreased with the percentage decrease in uric acid levels at a dose of 10 mg/Kg BB, 20 mg/Kg BB and 40 mg/Kg BB, respectively by 13.2%, 24.5% and 54.3%. The results of the One Way Anova statistical test showed a significant difference with P value = 0.010 (α <0.05). The concentration of the extract that gave the greatest reducing effect was the extract dose of 40mg/kgBB.